Vesicular Nucleotide Transport: A Brief History and the Vesicular Nucleotide Transporter as a Target for Drug Development - Hiasa, Miki; Togawa, Natsuko; Moriyama, Yoshinori (Current Pharmaceutical Design, 2014)
Neurons and neuroendocrine cells store nucleotides in vesicles and release them upon stimulation, leading to intercellular purinergic signaling. The molecular machinery responsible for the vesicular storage of nucleotides was a long standing enigma, however, recently the transporter involving in the process was identified. This article summarizes the history of vesicular storage of nucleotides and the identification of the vesicular nucleotide transporter (VNUT) responsible for the process. The significance of VNUT as a drug target to control purinergic chemical transmission is also discussed.
Keywords: purinergic chemical transmission